Development of project-based learning model based on ethno-steam to improve numeracy literacy skill - Haryanto Haryanto; Samsudi Samsudi; Mintarsih Arbarini (Himpunan Pengembang Kurikulum Indonesia, 2024)
21st-century learning is learning that prepares students to have the ability to think creatively, critically, and innovatively and master technology. This research aims to analyze and describe the development design, feasibility, and effectiveness of a project-based learning model based on ethno-steam (science, technology, engineering, mathematics, and art) to improve numeracy literacy skills. This research uses the R&D method with ADDIE (Analyze, Design, Development, Implementation, Evaluation). This research was conducted in class VIII MTsN 3 Lima Puluh Kota in mathematics. PjBL, STEAM, and Material experts have validated this learning model. The results of the expert validation obtained an average value of 91% with a very feasible category. The N-Gain results to determine the effectiveness of the ethno-STEAM-based project-based learning model to improve numeracy literacy skills obtained a value of 0.69 in the medium category. The Ethno-STEAM-based project-based learning model is classified as adequate based on the N-Gain results. Developing an ethno-STEAM-based project learning model (Science, Technology, Engineering, Art, and Mathematics) is highly recommended to be applied in mathematics learning and implementing Kurikulum Merdeka. Abstrak Pembelajaran abad 21 merupakan pembelajaran yang mempersiapkan peserta didik memiliki kemampuan berpikir kreatif, kritis, inovatif serta menguasai teknologi. Tujuan penelitian ini untuk menganalisis dan mendeskripsikan desain pengembangan, menganalisis dan mendeskripsikan kelayakan serta menganalisis dan mendeskripsikan efektivitas pembelajaran project-based learning model based ethno-steam (sains teknologi teknik seni matematika) dalam meningkatkan kemampuan literasi numerasi. Penelitian ini menggunakan metode R&D dengan ADDIE (Analyze, Design, Development, Implementation, Evaluation).Penelitian ini dilaksanakan di kelas VIII MTsN 3 Lima Puluh Kota pada mata pelajaran matematika. Model pembelajaran ini telah divalidasi oleh ahli PjBL, ahli STEAM dan ahli Materi. Hasil validasi ahli tersebut memperoleh nilai rata-rata sebesar 91% dengan kategori sangat layak. Hasil N-Gain untuk mengetahui keefektifan model project-based learning berbasis ethno-STEAM untuk meningkatkan kemampuan literasi numerasi memperoleh nilai sebesar 0,69 dengan kategori sedang. Berdasarkan hasil N-Gain penggunaan model project-based learning berbasis Ethno-STEAM tergolong efektif Pengembangan model pembelajaran proyek berbasis etno-STEAM (Science, Technology, Engineering, Art, and Mathematics) sangat dianjurkan untuk diterapkan dalam pembelajaran matematika, khususnya dalam menyambut kurikulum merdeka. Kata Kunci: Etno-STEAM; literasi numerasi; model pembelajaran berbasis proyek